Spin Crossover and Long‐Lived Excited States in a Reduced Molecular Ruby. Issue 32 (20th May 2020) - Becker, Patrick M.; Förster, Christoph; Carrella, Luca M.; Boden, Pit; Hunger, David; van Slageren, Joris; Gerhards, Markus; Rentschler, Eva; Heinze, Katja
Abstract: The chromium(III) complex [Cr III (ddpd)2 ] 3+ (molecular ruby; ddpd= N, N′ ‐dimethyl‐ N, N′ ‐dipyridine‐2‐yl‐pyridine‐2, 6‐diamine) is reduced to the genuine chromium(II) complex [Cr II (ddpd)2 ] 2+ with d 4 electron configuration. This reduced molecular ruby represents one of the very few chromium(II) complexes showing spin crossover (SCO). The reversible SCO is gradual with T 1/2 around room temperature. The low‐spin and high‐spin chromium(II) isomers exhibit distinct spectroscopic and structural properties (UV/Vis/NIR, IR, EPR spectroscopies, single‐crystal XRD). Excitation of [Cr II (ddpd)2 ] 2+ with UV light at 20 and 290 K generates electronically excited states with microsecond lifetimes. This initial study on the unique reduced molecular ruby paves the way for thermally and photochemically switchable magnetic systems based on chromium complexes complementing the well‐established iron(II) SCO systems. Abstract : Ruby‐reduced : Reduction of the molecular ruby [Cr III (ddpd)2 ] 3+ (ddpd= N, N′ ‐dimethyl‐ N, N′ ‐dipyridine‐2‐yl‐pyridine‐2, 6‐diamine) gives the genuine chromium(II) complex [Cr II (ddpd)2 ] 2+ showing spin crossover (SCO) with T 1/2 around room temperature. Geometric distortions and color changes accompany this reversible SCO. Excitation with UV light yields electronically excited states with microsecond lifetimes.